A comparative study of clinical effect on the Da Vinci surgical robot-assisted and laparoscopic-assisted distal subtotal gastrectomy for gastric cancer - Chenjun Tan (临床与病理杂志, 2026)
Objective: To evaluate the feasibility, safety and the clinical outcomes of the robotic distal gastrectomy for gastric cancer. Methods: We retrospectively analyzed the clinical and follow-up data of 113 cases underwent robotic distal gastrectomy from March 2010 to July 2013. Results: Compared with laparoscopic group, the robotic group had less intraoperative blood loss, more lymph nodes dissection (P<0.05). There was no significant difference in the incidence of postoperative complications and neutrophil-lymphocyte ratio between the two groups. The follow-up data showed that the 1-, 2- and 3-year survival rates were 91.7%, 77.4% and 72.9% in robotic group while they were 91.2%, 76.2% and 70.4% in laparoscopic group ,and the difference was not significant. Conclusion: Robotic distal gastrectomy for gastric cancer is safe and effective, and it has less harm to the patients, with less intraoperative blood loss, more lymph nodes dissection and quicker postoperative recover than laparoscopic surgery, so it is worthy of popularization and application.